Designing a Total Data Solution: Technology, Implementation, and Deployment - Burkey, Roxanne (CRC Press, 2009)
Your company's global competitiveness depends on the utilization and maintenance of information. Current data handling practices-storing, updating, and accessing data-can be either a problem or a significant strategic advantage for your company. Designing a Total Data Storage Solution: Technology, Implementation, and Deployment gives you the information you need to compare current technologies and determine which is best suited to your enterprise.